Urgensi Penerapan Layanan Jembatan Timbang Berbasiskan Digital Sebagai Inovasi Peningkatan Layanan di Pelabuhan Penyeberangan Amolengo Provinsi Sulawesi Tenggara - Rajulan, Muhammad; Ferima, Ferima; Herya, Bony; Hado, Hado; Satyadharma, Maudhy (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2025)
The current governance requires innovation so that it will have an impact on improving the quality of publik services. The transportation aspect must also present a breakthrough and innovation so that it has an impact on improving the safety and security of transportation services and also increasing the quality of service and satisfaction of service users. One of the innovations planned to be presented by the Southeast Sulawesi Provincial Transportation Agency is a digital-based weighbridge service. This study analyzes the urgency of implementing a digital-based weighbridge service at the Amolengo Ferry Port. This study uses a qualitative research approach using a descriptive method. The plan to implement a digital-based weighbridge service at the Amolengo Ferry Port is an innovation that must be implemented as soon as possible even though there are still many obstacles such as budget availability and minimal human resources for management. The recommendation from this study is to encourage collaboration with various parties (Collaborative Governance) both across government agencies, the private sector and local community participation so that existing problems can be found solutions and solutions.